Cross-Sectional Analysis of Oral Healthcare vs. General Healthcare Utilization in Five Low- and Middle-Income Countries - Susarla, Sita Manasa; Trimble, Margaret; Sokal-Gutierrez, Karen (Frontiers in Oral Health, 2022)
Oral health is integral to overall health and is often neglected, especially in low- and middle-income countries (LMICs). Oral disease, including untreated dental caries, affects nearly 3.5 billion people globally, contributing to poor health and quality of life. To examine the relationship between the utilization of general healthcare and oral healthcare, we conducted an exploratory cross-sectional study of first-visit interview data collected from a convenience sample of 3,422 low-income mothers and 4,324 children aged 6 months through 6 years participating in a community-based oral health and nutrition program in five LMICs (Ecuador, El Salvador, India, Nepal, and Vietnam) from 2006-2015. We used descriptive and exploratory association analysis to identify patterns of oral healthcare utilization for mothers and children compared to medical care utilization, specifically maternal prenatal care and child immunizations. Overall, 89.6% of the mothers had received prenatal care for at least one child, but only 76.4% had ever received dental care and 50% were currently suffering from oral health symptoms, primarily oral pain. Mothers who received prenatal care were significantly more likely to have accessed dental care compared to those who had not received prenatal care (OR = 2.62, 95% CI: 2.07, 3.32). Overall, 95.4% of the children had current immunizations, but only 30.1% had ever received dental care, and 32.4% were currently suffering from oral pain. Children whose immunizations were up-to-date were more likely to have received dental care, with a significant association in Ecuador (OR = 3.29, 95% CI: 2.06, 5.30). Compared to utilization of general healthcare, oral healthcare was under-utilized by mothers and children in our sample from five LMICs. Integration of prevention- and treatment-oriented oral healthcare into primary medical care services, particularly prenatal care and child immunization, could help increase access to oral healthcare and improve women’s and children’s oral health.